Action research living theory - Whitehead, Jack (Sage, 2006)
In Action Research: Living Theory, authors Jean McNiff and Jack Whitehead set out their vision of action research should be and can in the 21st Century. This brilliantly-written, passionate, and compelling book, defines the philosophy behind action research and the process of doing action research for all those interested in this fast growing area. It establishes the foundations of action research as a discipline, and roots action research as a compassionate, ethical, and politically-engaged form of inquiry. This book will be essential reading for all those with an interest in Action Research.